Incorporation of Class C and Class F Fly Ash in Concrete Mix: Effect on Rheological and Strength Properties - Saurav Kar; Puspendu Das; Pritha Das; Anup Kumar Mondal (Technological Innovation in Engineering Research Vol. 7, 2022)
Cement concrete is regarded as versatile material of construction development of various infrastructure in the modern civilized society. Fly ash, most probably, is considered as one of the potential supplementary cementious alternative to cement since decades. Fly ash, being a waste material generated from thermal power plants, is a pozzolanic substance containing aluminous and siliceous substance that reacts with calcium hydroxide to produce calcium silicate gel, instigates faster cement hydration. In this present study, an attempt is made to identify and analyze different factors which influence the reactivity of fly ash. Usage of fly ash in concrete leads to reduction in water demand and early-age strength while leads to higher later strength, durability, acid resistance and sulphate resistance, increased flowability, segregation and better rheological properties. In this present work, detailed study of the various mechanical properties (tensile, flexural and compressive strengths) as well as bond strengths is incorporated. This paper highlights detailed literature review on various strength properties of various concrete specimen conducted in past research works. This research investigation contains study on hardened fly ash - concrete composites with various proportions of fly ash (low content max. 50% with and without other chemical and mineral admixtures). Research investigation emphasizes multi-dimensional effects of chemical admixtures influences on the concrete properties as well as investigation of properties of high-volume fly ash to further support the case of fly ash-based structures